Emergente Herstellung von Temporalität in Texten.: Lexikalische, syntaktische und textuelle Perspektiven auf Jahres-gutachten des Sachverständigenrats für Wirtschaft - Jacob, Katharina (Linguistik Online, 2026)
This article investigates how time is verbalised and textualised, advancing the thesis that temporality emerges within and through both the structural and semantic dimensions of text. From a semasiological perspective, both explicit and implicit linguistic means are central; from an onomasiological viewpoint, elements of linguistic repertoire, syntax, and textual organization – though not inherently temporal – can acquire temporal function through patterned co-occurrence. Accordingly, temporality warrants examination not only in terms of localisation – how events are situated along a temporal axis – but also with regard to how they are interrelated within the text. As empirical data, the study draws on the ‘Annual Reports of the German Council of Economic Experts’ (Jahresgutachten des Sachverständigenrats für Wirtschaft (JGSW)), published between 1964 and 2023. In a first step, these reports are examined in their full-length versions using corpus-linguistic methods to identify and interpret explicit temporal lexis. In a second step, a detailed qualitative analysis delineates interpretive categories of temporal concepts and functions. The account of emergent temporality operates along a continuum between lexis and grammar, foregrounding the linearity and synchronicity inherent to textual organisation.